Febrile Infection-Related Epilepsy Syndrome (FIRES), a Possible Cause of Super-Refractory Status Epilepticus: A Case Report - Sahraoui, Houssam Eddine; Danaoui, Kaoutar; Sihami, Abdelaziz; Mouaffak, Youssef; Younous, Said (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Febrile infection-related epilepsy syndrome (FIRES) is a subset of NORSE that requires a febrile infection between 24 h and 2 weeks before the onset of refractory status epilepticus (SE), with or without fever at the onset of SE, and with no restriction to the age of the patient. The literature on FIRES is scarce. CASE PRESENTATION: This article reports a case of a patient of 8 years old without relevant family, psychosocial, prenatal or perinatal, or pathological history and normal neurodevelopment. The child consulted on a pediatric emergency with convulsive SE preceded 8 days before by otitis with acute fever managed with cephalosporin. Subsequently, seizures appeared in the following 48 h, characterized by generalized tonic-clonic seizures lasting 5–6 min. The seizures became more frequent until consciousness deteriorated, and motor SE appeared. In consequence, a coma was initiated, and the patient was hospitalized for emergency pediatric reanimation, where multifocal clonic and myoclonic seizures continued. A lumbar puncture with polymerase chain reaction was done twice and returned negative. Two magnetic resonance imaging scans were performed: the first was normal and the second, after 20 days in the hospital, showed cortical damage with SE. Different anticonvulsant treatments were used for 4 weeks: Valproic acid, clobazam, ketamine, levetiracetam for 24 days, and relay to, brivaracetam used in the treatment of epilepsy to control focal seizures; propofol, midazolam, and some antiepileptic drugs were used simultaneously and at maximum recommended doses, achieving a poor initial response, but eventually leading to total crisis control. The patient receives immunoglobulin for 2 days 1 g/kg/J. A ketogenic diet aimed at therapy and known antiepileptic properties, rich in lipids, and low in sugars, causing ketonemia in non-surgical drug-resistant epilepsies, was used for our patient with an efficacy that proved to be remarkable on the frequency of undergoing seizures, his tolerance was good. The diet can be maintained for 20 days without incident, in particular, with no episode of hypoglycemia. Electroconvulsive therapy (formerly called sismotherapy, electronarcosis, or shock therapy) is a therapeutic tool used in several psychiatric illnesses was also used with different frequencies for our patients twice a week with no favorable response. The evolution was marked by the aggravation of the patient following diffuse cerebral edema resulting in cardiac arrest and non-response to resuscitation measures, the patient declared at 07 AM on February 27, 2023. CONCLUSION: FIRES is a rare epilepsy syndrome of unclear aetiology in which children, usually of school age, suddenly develop very frequent seizures after a mild febrile illness. Seizures in FIRES are typically difficult to treat, and the prognosis is poor.